Dekonstruksi Sosial terhadap Stereotip Gender dalam Budaya Olahraga Formula 1 - Averilio Raharja; Refti Handini =; Ahmad Ridwan; Moh. Mudzakkir (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Sports not always been a neutral space, but rather an arena for the production and reproduction of power relations, ideologies, and social constructs. Formula 1 (F1) is a global sport laden with symbols of masculinity, capitalism, and exclusivity, which often marginalizes women in fandom culture. This study aims to deconstruct gender stereotypes about female F1 fans, who are often reduced to being “aesthetic fans” or merely following trends because of their interest in the appearance of F1 drivers, rather than the thchnical aspects of the sport. Using Michel Foucault’s discourse analysis approach, this study highlights how power works through the media, online communities, and social interactions to normalize gender hierarchies in F1 fandom culture. The research data was obtained through content and comments on the Instagram account @infipop.id, which shows how stereotypes are produced and challenged by resistance from female F1 fans. The results of the study show that social media has become a space for social deconstruction, where women associate their identities as true F1 fans through alternative narratives, technical analysis, and digital communities. This study contributes to gender and sports studies by emphasizing the importance of social deconstruction in creating a more inclusive and egalitarian fandom space.